Reproductive Health of Female Patients with Connective Tissue Dysplasia - Irina V. Karachentsova; Anastasia V. Goryainova; Elena V. Sibirskaya; Marina Yu. Alekhina; Amina F. Askerova (Union of pediatricians of Russia, 2023)
Connective tissue dysplasia is congenital anomaly manifesting as different organ's and system's alterations: locomotor, skin, visceral dysfunctions. This article presents literature review covering such topical issues as female reproductive system features affected by mesenchymal pathology (undifferentiated forms of connective tissue dysplasia) and its medicamentous management (microelements, hormonal drugs, adaptogens). The analysis of original studies on this topic has revealed that connective tissue dysplasia has significant effect on female reproductive function development and can be complicated by various menstrual dysfunctions (hypomenorrhea syndrome, oligomenorrhea, opsomenorrhea, uterine bleedings, and secondary amenorrhea) as well as by endocrine changes (anti-Mullerian hormone deficiency, hypoprolactinaemia, hypoestrogenemia, etc.). Gestation and delivery features in patients with connective tissue dysplasia (preeclampsia, premature birth, and fetal abnormalities) were also revealed.